High performance and near body temperature induced self-healing thermoplastic polyurethane based on dynamic disulfide and hydrogen bonds. (1st February 2021) - Wu, Haohao; Liu, Xiangdong; Sheng, Dekun; Zhou, Yan; Xu, Shaobin; Xie, Haopu; Tian, Xinxin; Sun, Yinglu; Shi, Biru; Yang, Yuming
Abstract: It is necessary to develop polymer materials with excellent mechanical properties and can be quickly repaired under reasonable conditions. However, it is difficult to simultaneously optimize the mechanical properties and repair conditions as they have conflicting realization requirements. In this study, we prepare a thermoplastic polyurethane (I-4-P-HM) containing two kinds of alicyclic isocyanate with a tensile strength and toughness of 11.35 MPa and 64.1 MJ m −3, respectively. The mechanical properties of the cut and spliced I-4-P-HM films can be completely restored to their original values at near body temperature (40 °C) in only 2 h. In I-4-P-HM, isophorone diisocyanate (IPDI) directly connect to aromatic disulfide that enables a more efficient exchange of the aromatic disulfides, while dicyclohexylmethane 4, 4′-diisocyanate (HMDI) with a symmetrical alicyclic structure endows the TPU with better mechanical properties. The two work together to make polyurethane have good mechanical properties and can be repaired quickly under mild condition. Furthermore, we carried out the scratch recovery experiments on I-4-P-HM covered with a layer of conductive silver paste, and the results indicate that this TPU has the potential to be applied in the flexible electronics industry. Graphical abstract: I-4-P-HM prepared by two different kinds alicyclic isocyanates not only have excellent mechanical properties, but also can be quickly repaired at near body temperature (40 °C). Image 1 Highlights: Polyurethanes are prepared from mixed isocyanates. The mechanical strength and toughness of I-4-P-HM can be achieved 11.35 MPa and 64.1 MJ m 3, respectively. I-4-P-HM can be completely repaired in 2 h at 40 °C. The polyurethanes obtained in this paper have certain repairing ability at near body temperature.